10Be dating of the Main Terrace level in the Amblève valley (Ardennes, Belgium): new age constraint on the archaeological and palaeontological filling of the Belle‐Roche palaeokarst. (13th February 2014) - Rixhon, Gilles; Bourlès, Didier L.; Braucher, Régis; Siame, Lionel; Cordy, Jean‐Marie; Demoulin, Alain
<x xml:space="preserve">Abstract</x> It is still disputed whether very old archaeological and palaeontological remains found in the Belle‐Roche palaeocave (eastern Belgium) pertain to the Early (∼1 Ma) or Middle (∼0.5 Ma) Pleistocene. Here, in situ‐produced cosmogenic 10Be concentrations from a depth profile in nearby sediments of the Belle‐Roche terrace (Amblève Main Terrace level) are used as an indirect solution of this chronological issue. The distribution of 10Be concentrations in the upper 3 m of this profile displays the theoretically expected exponential decrease with depth. Assuming a single exposure episode, we obtain a best fit age of 222.5±31 ka for the time of terrace abandonment. However, below 3 m, the 10Be concentrations show a marked progressive increase with depth. This distinctive cosmogenic signal is interpreted as the result of slow aggradation of the fluvial deposits over a lengthy interval. Modelling of the whole profile thus suggests that the onset of the terrace formation occurred at around 550 ka, with a sediment accumulation rate of ∼20 mm ka−1. Based on two slightly different reconstructions of the geomorphic evolution of the area and a discussion of the temporal link between the cave and Main Terrace levels, we conclude that the fossil‐bearing layers in the palaeokarst pertain most probably to MIS 14–13, or possibly MIS 12–11. This age estimate for the large mammal association identified in the Belle‐Roche palaeokarst and the attribution to MIS 14–13 of a similar fauna found in the lowermost fossiliferous layers of the Caune de l'Arago (Tautavel) are in mutual support. Our results therefore confirm the status of the Belle‐Roche site as a reference site for the Cromerian mammal association in NW Europe.